Transforming learning environments strategies to shape the next generation - Miller, Fayneese S. (Advances in educational administration ;, 2012)
With the influence and pressures of the globalized economy, education systems are at a crossroads and need to find a place and/or identity that reflect new or transformed realities for learning environments. Questions such as to what extent, in what way, and how are we doing will need to be raised and answered before learning environments can begin the work necessary to create people who are ready to enter the globalized workforce. This book will present chapters written from a variety of perspectives to address the question "what is needed within systems of education to prepare the next generation of leaders for a competitive global environment?" The authors focus on such topics as online learning, technology, leadership, and English Language Learners to show the challenges to traditional educational practices and the ways in which learning environments are responding to the new reality of globalization.